Strong ties inside and outside the neighbourhood. An exploratory analysis of the spatial dimension of ego/alter relations in three urban settings in Vienna - Kohlbacher,Josef (2013)
Regarding the spatial dimension of ego/alter relations, the fact whether egos and alters live within the same neighbourhood and the consequences thereof are heavily debated. Some authors argue that a network consisting mostly of people who live in the same urban area may result in lower socio-economic opportunities. Another strand of research emphasizes the importance of strong ties on the local level for neighbourhood embeddedness and social cohesion. In this article the role of the neighbourhood (a) in the formation of strong ties, (b) as the place where strong ties currently live and (c) as a meeting place for people sharing strong ties is investigated for three neighbourhoods in Vienna. In line with previous research results, it turns out that in the socially marginalized remote setting, strong ties are more often neighbourhood-based and less often interethnic. In the more affluent neighbourhood, strong ties are not so strongly bound to the neighbourhood, but are more spatially dispersed.